A comparative study on phytochemical constituents and antimicrobial activity of Alternanthera sissoo extracts - Khairul Anuar, 'Aina Khalida (Enhanced Knowledge in Sciences and Technology, 2022)
Plant contains numerous bioactive compounds which can inhibit antimicrobial activity and therefore used as antimicrobial drugs in traditional medicine. In this study, the objectives are to identify the qualitative phytochemical components present in Alternanthera sissoo extracts under different processing forms and to evaluate the antimicrobial microbial activity of Bacillus cereus and Escherichia coli of Alternanthera sissoo extracts under different processing forms. The method used are qualitative phytochemical screening which revealed the presence of flavonoids, terpenoids, tannins and saponins. Antimicrobial activity performed disc diffusion and agar well diffusion method to measure the inhibition zones of Gram-positive and Gram-negative bacteria. The phytochemical screening shows that A. sissoo contains terpenoids in any processing forms. Fresh and dry sample do not contain flavonoids but boiled and steam blanch sample. Saponins are presence in fresh and dry sample and tannins only presence in dry sample. The ethanolic extract of A. sissoo showed moderate antimicrobial activity against B. cereus in boiled sample (19 mm) followed by steam blanch sample (14 mm) and none against E. coli. This finding showed that H. sabdariffa had antimicrobial activity against pathogenic bacteria and hold great promise as a natural product in antimicrobial agents.